PEMETAAN STATUS UNSUR HARA FOSFOR DAN KALIUM DI PERKEBUNAN NANAS (Ananas comosus L. Merr) RAKYAT DESA PANRIBUAN KECAMATAN DOLOK SILAU KABUPATEN SIMALUNGUN - Muhammad Afwan Hadi; Razali Razali; Fauzi Fauzi (Jurnal Agroekoteknologi, 2014)
ABSTRACTMapping of Phosphorus and Potassium status on Pineapple people plantations in the villagePanribuan Sub District Dolok Silau District Simalungun Leading by Ir. Razali, MP. andIr. Fauzi, MP. This research purpose to make a mapping phosphorus and potassium status onPineapple people plantations in the village Panribuan Sub Dolok Silau Simalungun District. Theresearch started to do on October 2012 until January 2013. Method of taking sample used the freemethod grid survey with detail scale and use correlation method to analysis data, with interpretatingin mapping Nitrogen and C-Organic. Parameters to be analyzed are P2O5 and K2O.The result ofresearch shows that P2O5 status devided by four status ; low (6.5 Ha), medium (11.63 Ha), high (8.7Ha) and very high (8.61 Ha. K2O devided by four status ; very low (20.09 Ha), low (11.76 Ha),medium (3.28 Ha), and high (0.31 Ha). Satistic analysis using SPSS known that the no effect on anincrease in production by P2O5 but K2O give effect on an decrease in pineapple production.Keywords : mapping, P2O5, K2O, and production